Comparison of Esterase Isozyme Variability in Some Selected Tissues of the Asian and African Catfishes (Siluriformes: Clariidae) (Bangladesh Journal of Zoology, 2012)
Variation in esterase isozymes expression of 19 different tissues of the Asian catfish (Clarias batrachus) and African catfish (C. gariepinus) was studied. These tissues were: liver, anterior muscle, mid muscle, tail muscle (ventral region), tail muscle (tip region), buccal muscle, stomach, foregut, midgut, hindgut, kidney, gill, heart, eye (lens), eye (black portion), pelvic muscle, fore-, mid- and hind-brain. Maximum five esterase bands, viz. Est-11.83, Est-21.50, Est-31.15, Est-41.00 and Est- 50.17 were observed in the Asian catfish and four bands, viz. Est-21.50, Est-31.15, Est-41.00 and Est-50.17 in the African catfishes. Tissue specific localization of the isozymes was observed in both Asian and African catfishes. Comparatively higher esterase activity was found in digestive tissues. Higher number of esterase bands was found in C. batrachus which seems to be an indication of its greater allelic variation in esterases than those in the C. gariepinus. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12893 Bangladesh J. Zool. 40(1): 43-50, 2012